The priority of procedure and the neglect of evidence and proof: facing facts in international criminal law - Roberts, Paul (Oxford University Press, 2015)
This article concerns the role and value of procedural and evidentiary scholarship in the rapidly developing field of International Criminal Law (ICL). It extrapolates and adapts to the international context two, distinct but related, lines of argument previously pitched at the domestic level. The first, broadly speaking jurisprudential, argument asserts ‘the priority of procedure’, challenging the widespread assumption that procedure is the merely adjectival handmaiden of substantive criminal law. The second, essentially methodological, argument advocates a conception of ‘evidence and proof’ extending beyond doctrinal rules to encompass sustained analysis of factual evidence, logical inferential reasoning, and forensic argumentation. One particular analytical method — Wigmore charting — is illustrated as offering a set of practical tools for supporting criminal litigation, in international no less than domestic proceedings. Though ICL scholarship has from the outset taken a commendably keen interest in procedural questions, there is scope for broader and deeper engagement with procedural and evidentiary issues, with potential for enriching both the theory and the practice of international criminal law. (And ICL might then repay the compliment by broadening the conventional disciplinary horizons of Evidence and Proof and Criminal Law Theory scholarship.)